79
$\begingroup$

$$\int_0^1\frac{\mathrm dx}{\sqrt{1-x}\ \sqrt[4]x\ \sqrt[4]{2-x\,\sqrt3}}\stackrel?=\frac{2\,\sqrt2}{3\,\sqrt[8]3}\pi\tag1$$ The equality numerically holds up to at least $10^4$ decimal digits.

Can we prove that the equality is exact?

An equivalent form of this conjecture is $$I\left(\frac{\sqrt3}2;\ \frac14,\frac14\right)\stackrel?=\frac23,\tag2$$ where $I\left(z;\ a,b\right)$ is the regularized beta function.


Even simpler case: $$\int_0^1\frac{\mathrm dx}{\sqrt{1-x}\ \sqrt[6]{9-x}\ \sqrt[3]x}\stackrel?=\frac\pi{\sqrt3},\tag3$$ which is equivalent to $$I\left(\frac19;\ \frac16,\frac13\right)\stackrel?=\frac12.\tag4$$


A related question.

$\endgroup$
  • 46
    $\begingroup$ Is it a routine of yours to randomly choose equations in the morning, approximate them by the afternoon, and conjecture them in the night? $\endgroup$ – chubakueno Oct 27 '13 at 5:36
  • 5
    $\begingroup$ Where is this coming from ? $\endgroup$ – Claude Leibovici Oct 27 '13 at 5:40
  • 26
    $\begingroup$ @chubakueno I would say it's a hobby. $\endgroup$ – Vladimir Reshetnikov Oct 27 '13 at 5:40
  • 11
    $\begingroup$ I am sure you know that this is a hypergeometric function$$ \int_{0}^1 \frac{dx }{\sqrt{1-x} \sqrt[4]{x}\sqrt[4]{ 2-x \sqrt{3}}}=\frac{2^{9/4} \pi^{3/2} }{\Gamma^2\left(\frac14\right)}{}_2F_1\left( \frac14, \frac34, \frac54,\frac{\sqrt{3}}{2} \right) $$ Your answer almost certainly follows from some combination of its quadratic (or higher-order) transformations. But to be honest, I don't see what can one learn in the course of such calculation. $\endgroup$ – Start wearing purple Oct 27 '13 at 5:45
  • 10
    $\begingroup$ Vladimir, you've been posting a lot of conjectures about integrals of this form. Given as @O.L. says that they seem to be related to Hypergeometric functions, could your questions be more systematically written down as - "How can we simplify the hypergeometric function for various inputs?" $\endgroup$ – Bennett Gardiner Oct 27 '13 at 5:51
90
+150
$\begingroup$

For $\alpha, \beta, \gamma \in (0,1)$ satisfying $\alpha+\beta+\gamma = 1$ and $\mu \in \mathbb{C} \setminus [1,\infty)$, define

$$ F_{\alpha\beta}(\mu) = \int_0^1\frac{dx}{x^\alpha(1-x)^\beta(1-\mu x)^\gamma} \quad\text{ and }\quad \Delta = \frac{\Gamma(1-\alpha)\Gamma(1-\beta)}{\Gamma(1+\gamma)} $$ When $|\mu| < 1$, we can rewrite the integral $F_{\alpha\beta}(\mu)$ as

$$\begin{align} F_{\alpha\beta}(\mu) = & \int_0^1 \frac{1}{x^\alpha(1-x)^{\beta}}\left(\sum_{n=0}^{\infty}\frac{(\gamma)_n}{n!}\mu^n x^n\right) dx = \sum_{n=0}^{\infty}\frac{(\gamma)_n}{n!}\frac{\Gamma(n+1-\alpha)\Gamma(1-\beta)}{\Gamma(n+1+\gamma)}\mu^n\\ = & \Delta\sum_{n=0}^{\infty}\frac{(\gamma)_n (1-\alpha)_n}{n!(\gamma+1)_n}\mu^n = \Delta\gamma \sum_{n=0}^{\infty}\frac{(1-\alpha)_n}{n!(\gamma+n)}\mu^n \end{align}$$ This implies $$ \mu^{-\gamma} \left(\mu\frac{\partial}{\partial \mu}\right) \mu^{\gamma} F_{\alpha\beta}(\mu) = \Delta\gamma \sum_{n=0}^{\infty}\frac{(1-\alpha)_n}{n!}\mu^n = \Delta\gamma\frac{1}{(1-\mu)^{1-\alpha}} $$ and hence $$F_{\alpha\beta}(\mu) = \Delta\gamma \mu^{-\gamma} \int_0^\mu \frac{\nu^{\gamma-1}d\nu}{(1-\nu)^{1-\alpha}} = \Delta\gamma \int_0^1 \frac{t^{\gamma-1} dt}{(1-\mu t)^{1-\alpha}} = \Delta \int_0^1 \frac{dt}{(1 - \mu t^{1/\gamma})^{1-\alpha}}$$

Notice if we substitute $x$ by $y = 1-x$, we have

$$F_{\alpha\beta}(\mu) = \int_0^1 \frac{dy}{y^\beta(1-y)^\alpha(1-\mu - \mu y)^{\gamma}} = \frac{1}{(1-\mu)^\gamma} F_{\beta\alpha}(-\frac{\mu}{1-\mu})$$

Combine these two representations of $F_{\alpha\beta}(\mu)$ and let $\omega = \left(\frac{\mu}{1-\mu}\right)^{\gamma}$, we obtain

$$F_{\alpha\beta}(\mu) = \frac{\Delta}{(1-\mu)^{\gamma}}\int_0^1 \frac{dt}{( 1 + \omega^{1/\gamma} t^{1/\gamma})^{1-\beta}} = \frac{\Delta}{\mu^\gamma}\int_0^\omega \frac{dt}{(1 + t^{1/\gamma})^{1-\beta}}$$

Let $(\alpha,\beta,\gamma) = (\frac14,\frac12,\frac14)$ and $\mu = \frac{\sqrt{3}}{2}$, the identity we want to check becomes

$$\frac{\Gamma(\frac34)\Gamma(\frac12)}{\Gamma(\frac54) (\sqrt{3})^{1/4}}\int_0^\omega \frac{dt}{\sqrt{1+t^4}} \stackrel{?}{=} \frac{2\sqrt{2}}{3\sqrt[8]{3}} \pi\tag{*1}$$

Let $K(m)$ be the complete elliptic integral of the first kind associated with modulus $m$. i.e.

$$K(m) = \int_0^1 \frac{dx}{\sqrt{(1-x^2)(1-mx^2)}}$$ It is known that $\displaystyle K(\frac12) = \frac{8\pi^{3/2}}{\Gamma(-\frac14)^2}$. In term of $K(\frac12)$, it is easy to check $(*1)$ is equivalent to

$$\int_0^\omega \frac{dt}{\sqrt{1+t^4}} \stackrel{?}{=} \frac23 K(\frac12)\tag{*2}$$

To see whether this is the case, let $\varphi(u)$ be the inverse function of above integral. More precisely, define $\varphi(u)$ by following relation:

$$u = \int_0^{\varphi(u)} \frac{dt}{\sqrt{1+t^4}}$$

Let $\psi(u)$ be $\frac{1}{\sqrt{2}}(\varphi(u) + \varphi(u)^{-1})$. It is easy to check/verify $$ \varphi'(u)^2 = 1 + \varphi(u)^4 \implies \psi'(u)^2 = 4 (1 - \psi(u)^2)(1 - \frac12 \psi(u)^2) $$

Compare the ODE of $\psi(u)$ with that of a Jacobi elliptic functions with modulus $m = \frac12$, we find

$$\psi(u) = \text{sn}(2u + \text{constant} | \frac12 )\tag{*3}$$

Since we are going to deal with elliptic functions/integrals with $m = \frac12$ only, we will simplify our notations and drop all reference to modulus, i.e $\text{sn}(u)$ now means $\text{sn}(u|m=\frac12)$ and $K$ means $K(m = \frac12)$.

Over the complex plane, it is known that $\text{sn}(u)$ is doubly periodic with fundamental period $4 K$ and $2i K$. It has two poles at $i K$ and $(2 + i)K$ in the fundamental domain. When $u = 0$, we want $\varphi(u) = 0$ and hence $\psi(u) = \infty$. So the constant in $(*3)$ has to be one of the pole. For small and positive $u$, we want $\varphi(u)$ and hence $\psi(u)$ to be positive. This fixes the constant to $i K$. i.e.

$$\psi(u) = \text{sn}(2u + iK )$$

and the condition $(*2)$ becomes whether following equality is true or not.

$$\frac{1}{\sqrt{2}} (\omega + \omega^{-1}) \stackrel{?}{=} \text{sn}( \frac43 K + i K)\tag{*4}$$

Notice $ 3( \frac43 K + i K) = 4 K + 3 i K $ is a pole of $\text{sn}(u)$. if one repeat apply the addition formula for $\text{sn}(u+v)$

$$\text{sn}(u+v) = \frac{\text{sn}(u)\text{cn}(v)\text{dn}(v)+\text{sn}(v)\text{cn}(u)\text{dn}(u)}{1-m\,\text{sn}(u)^2 \text{sn}(v)^2}$$

One find in order for $\text{sn}(3u)$ to blow up, $\text{sn}(u)$ will be a root of following polynomial equation: $$3 m^2 s^8-4 m^2 s^6-4 m s^6+6 m s^4-1 = 0$$ Substitute $m = \frac12$ and $s = \frac{1}{\sqrt{2}}(t+\frac{1}{t})$ into this, the equation $\omega$ need to satisfy is given by:

$$(t^8 - 6 t^4 - 3)(3 t^8 + 6 t^4 - 1 ) = 0$$

One can check that $\omega = \sqrt[4]{\frac{\sqrt{3}}{2-\sqrt{3}}}$ is indeed a root of this polynomial. As a result, the original equality is valid.

$\endgroup$
  • 8
    $\begingroup$ A nice solution! (+1) Can we verify the other integrals in the same way? $\endgroup$ – Shobhit Bhatnagar Oct 31 '13 at 9:35
  • 3
    $\begingroup$ @Integral, I don't know but I fear the chance is slim. The radicals in the other question has degree > 4! So the functions involved should be hyper-elliptic instead of elliptic functions. Without an elliptic function around, it is sort of hard (at least for me) to impose non-trivial polynomial constraints on the parameters/values in the corresponding integrals. $\endgroup$ – achille hui Oct 31 '13 at 9:52
  • 5
    $\begingroup$ @achillehui This is brilliant! What about the integral $(3)$ from my question above? $\endgroup$ – Vladimir Reshetnikov Oct 31 '13 at 16:24
  • 14
    $\begingroup$ @VladimirReshetnikov Let $I(s) = \int_0^{s} \frac{dt}{\sqrt{1+t^6}}$, it is easy to verify (3) is equivalent to $I(\frac{1}{\sqrt{2}}) = \frac12 I(\infty)$. If I didn't make any mistake, then $$\frac{(1-\sqrt{3})s^2+1}{(1+\sqrt{3})s^2+1} = \text{cn}\left( 2\sqrt[4]{3} I(s)\,\Big|\,\frac{2+\sqrt{3}}{4} \right)$$ and (3) can be verified using the double angle formula for $\text{cn}(\cdot)$. $\endgroup$ – achille hui Nov 1 '13 at 2:59
16
$\begingroup$

Here is another approach for evaluating the integral (3).

Using @achille hui's transformation, we can write

$$ I=\int_0^1\frac{dx}{\sqrt[3]{x}\sqrt{1-x}\sqrt[6]{9-x}}= \frac{4\pi^2 2^{\frac{1}{3}}}{\Gamma\left(\frac{1}{3}\right)^3}\int_0^\frac{1}{\sqrt{2}}\frac{1}{\sqrt{1+x^6}}dx $$ Using the substitution $x=\sqrt{t}$, we get $$ I=\frac{\pi^2 2^{\frac{4}{3}}}{\Gamma\left(\frac{1}{3}\right)^3}\int_0^\frac{1}{2}\frac{1}{\sqrt{t+t^4}}dt $$ We can now transform this integral into a beta integral using the substitution $t=\frac{1-y}{2+y}$. This gives us

\begin{align*} I &= \frac{\pi^2 2^{\frac{4}{3}}}{\Gamma\left(\frac{1}{3}\right)^3} \int_0^1\frac{1}{\sqrt{1-y^3}}dy \\ &= \frac{\pi^2 2^{\frac{4}{3}}}{3\Gamma\left(\frac{1}{3}\right)^3}B\left(\frac{1}{3},\frac{1}{2} \right) \\ &= \frac{\pi^2 2^{\frac{4}{3}}}{3\Gamma\left(\frac{1}{3}\right)^3}\left( \frac{\sqrt{3}\Gamma\left(\frac{1}{3}\right)^3}{\pi 2^{\frac{4}{3}}}\right) \\ &= \frac{\pi}{\sqrt{3}} \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.